A representação visual da mulher negra e suas re(produções) no curso de design da UFMA - PEREIRA, Danielle Cristina dos Santos (2024)
This research analyzes the contributions of the Narrative Research Group in Innovation, Design and Anthropology (NIDA) of the Design course at the Federal University of Maranhão (UFMA) in creating visual representations of black Brazilian women. It maps the visual representations of black women in NIDA productions and identifies the references used in the creation of these visual representations, problematizing how the use of these visual representations relates to racist and sexist stereotypes about black women that are widely propagated in society. It discusses the places where racial and gender issues permeate the training of designers, especially the visual representations of ways of life and of Afro-descendant women. To achieve this, this study uses a qualitative approach with literature review, documentary research, open interviews and analysis of visual representations using the still image analysis method of Mendes (2019). The anti-racist, Afrocentric and decolonial perspective supports the theoretical framework composed by: Hall (2016), Asante (2020), Collins (2019), Ballestrin (2013) among other scholars. In an intersecting way, we discuss design based on the Design for Social Innovation approach by Manzini (2017) with a focus on the Diversity, Culture and Inclusion Research Line, of the Postgraduate Program in Education (PPGE/UFMA). The theoretical discussions and the analysis of visual representations concluded that the deconstruction of the negative imaginary in relation to black women involves raising awareness about the need for black women to be perceived as agents, as producers of knowledge and for their perceptions of themselves to be highlighted in all spaces..